PENYUSUNAN SOAL SUMATIF BAHASA JERMAN - AL IMA, SELFI (LATERNE, 2017)
Replacement of Education Unit Level Curriculum (KTSP) with Curriculum 2013 (K13) causes some differences, the most prominent by Basic Competence is different so that the model of formative and summative test / evaluation is different. This difference raises the topic of the problem of how to model the summative question correctly and appropriately for evaluation and in accordance with K13. To demonstrate a valid and reliable summative test using qualitative and quantitative methods. Qualitative method use when the preparation in arranging of the sumative test  from various sources such as UAN German in 2008-2014. Quantitative Method on validity and realibility of item test. To get the data can be tested matter in school to know the level of validity and reliability item. The results of the first stage of 40 items are 17 items of invalidity, including numbers 1, 2, 3, 4, 6, 7, 8, 9, 10, 11, 12, 14, 17, 19, 24, 39, and 40. So that the valid item is 23 items. Results of the second stage of the 23 questions is 1 item of invalidity, the number is 12. So that the remaining 22 Items are valid. The results of the first and second stages contain only 22 valid items, so that in the third stage only 22 items are tested. Results from the third stage is an invalidity item of 22 items. Because assessed three stages have given enough results to state the feasibility of the test, so a matter of worth use only amounted to 21 items. Keywords: test, summative, validity, reliability